Correlations in Rosenzweig and Levinas - Gibbs, Robert, 1958- (Princeton University Press, 1992)
Robert Gibbs radically revises standard interpretations of the two key figures of modern Jewish philosophy -- Franz Rosenzweig, author of the monumental Star of Redemption, and Emmanuel Levinas, a major voice in contemporary intellectual life, who has inspired such thinkers as Derrida, Lyotard, Irigaray, and Blanchot. Rosenzweig and Levinas thought in relation to different philosophical schools and wrote in disparate styles. Their personal relations to Judaism and Christianity were markedly dissimilar. To Gibbs, however, the two thinkers possess basic affinities with each other. The book offers important insights into how philosophy is continually being altered by its encounter with other traditions.